ANALISIS KOSA KATA DAN WACANA BAHAN AJAR KOMPREHENSIF “HANYU” - Resna Aprilia Citra Ranti; Lily Thamrin; Lusi Tjen (Universitas Tanjungpura, 2019)
AbstractTeaching Mandarin has three elements, there is teacher, students and teaching material. In the process of learning Mandarin the relationship between these three is very close. To support the teacher that being able to prepare the quality lessons, the selection of teaching materials is very important. The writer makes the book of Hanyu vol. 1, 2 and 3 as the main object of this research. The aim is to examine the arrangement of vocabulary and discourse from the book. In addition to comprehend the assessment of students and teacher in use of this book. From the result of this research, the writer found that the vocabulary selection from vol. 1, 2, and 3 are mostly from words group level one and two. This shows that the books “Hanyu” vol. 1, 2 , and 3 are suitable for the needs of beginner level students. From the viewpoint of students class 7, 8 and 9 that they was satisfied with the preparation book of Hanyu, but the difficulty of discourse that is not accompanied by hanyu pinyin still quite high. In other that, the teacher Mandarin who used this books measure that the preparation of words and the discourses do not meet the requirement of students need when learning process is ongoing. Keywords : Teaching Materials Comprehensive, Hanyu, Vocabulary, Discourse, Assesment of Teaching Materials.